PRODUCTION, PURIFICATION AND CHARACTERISATION OF LASPARAGINASE FROM A SOIL ISOLATE GRIMONTIA HOLLISAE (VIBRIO) - C.N.KHOBRAGADE,; SHWETA R GOPHANE,; MENKA G JAYEBHAYE, (International Journal of Pharma and Bio Sciences, 2015)
L-asparaginase is an anti-cancer enzyme used in lymphoblastic leukaemia chemotherapy. Bacterial isolates were screened for potential producers of L-asparaginase using a phenol red indicator in growth medium and those microbial culture displayed pink red coloured colony was selected for further studies and was identified as Grimontia hollisae (Vibrio) by using fatty acid methyl ester (FAME) analysis. The enzyme production was carried out by submerged fermentation. The enzyme was partially purified by ammonium sulphate precipitation and dialysis was carried out to remove the excess salt. A Lineweaver-Burk analysis showed a Km value of 5.95 mM and Vmax of 0.588 IU/min. The characterised enzyme exhibited maximal enzyme activity at pH 8 and temperature 37°C. The activity of L-asparaginase is activated by mono-cations K+, Na+ and various effectors including 2-mercaptoethanol, whereas it is moderately inhibited by various divalent ions Hg++, Cu++ and Zn++. Substrate specificity studies indicated that, L-asparaginase has greater affinity towards L-asparagine. The amino acid composition of L-asparaginase was also determined.